Rates of lobar atrophy in asymptomatic MAPT mutation carriers. Issue 1 (30th July 2019) - Chen, Qin; Boeve, Bradley F.; Senjem, Matthew; Tosakulwong, Nirubol; Lesnick, Timothy G.; Brushaber, Danielle; Dheel, Christina; Fields, Julie; Forsberg, Leah; Gavrilova, Ralitza; Gearhart, Debra; Graff‐Radford, Jonathan; et al.
Abstract: Introduction: The aim of this study was to investigate the rates of lobar atrophy in the asymptomatic microtubule‐associated protein tau ( MAPT ) mutation carriers. Methods: MAPT mutation carriers (n = 14; 10 asymptomatic, 4 converters from asymptomatic to symptomatic) and noncarriers (n = 13) underwent structural magnetic resonance imaging and were followed annually with a median of 9.2 years. Longitudinal changes in lobar atrophy were analyzed using the tensor‐based morphometry with symmetric normalization algorithm. Results: The rate of temporal lobe atrophy in asymptomatic MAPT mutation carriers was faster than that in noncarriers. Although the greatest rate of atrophy was observed in the temporal lobe in converters, they also had increased atrophy rates in the frontal and parietal lobes compared to noncarriers. Discussion: Accelerated decline in temporal lobe volume occurs in asymptomatic MAPT mutation carriers followed by the frontal and parietal lobe in those who have become symptomatic. The findings have implications for monitoring the progression of neurodegeneration during clinical trials in asymptomatic MAPT mutation carriers. Highlights: The trajectory change of brain atrophy on longitudinal magnetic resonance imaging collected over 10 years was investigated in asymptomatic microtubule‐associated protein tau ( MAPT ) mutation carriers. A sequential pattern of regional cortical atrophy rates involving the temporal lobe cortex early on, followed by the frontal and parietal lobe cortices in MAPT mutation carriers as they transition from asymptomatic stage to symptomatic stage, was described. Our findings support the clinical utility of using longitudinal regional volumes for monitoring the neurodegenerative disease progression in MAPT mutation carriers starting from the asymptomatic stage.